Enhancing Physical Science Education: The Integration of Digital Practical Work in Teaching Electrodynamics for Experiential Learning - Moloi, Mabel; Matabane, Mogalatjane Edward (Research in Social Sciences and Technology- OpenED Network, 2024)
Digital practical work (DPW) has emerged as a highly effective and indispensable component of science education, enhancing and extending traditional laboratory experiences. DPW aims to complement physical laboratory experiments, particularly those that teachers may find challenging to conduct or lack the confidence to perform. In this study, a content training workshop on electrodynamics was implemented to showcase DPW's effectiveness. The workshop was designed to equip in-service physical science teachers with the skills needed for integrating digital tools into their teaching methods. To gather comprehensive data, the study utilized video recordings, discussions, and evaluation reports, providing rich qualitative evidence of DPW's effectiveness. These methods captured teachers' understanding of electromagnetic concepts, their experiences, and their perceptions of DPW. The findings revealed that DPW significantly enhanced teachers' knowledge of electrodynamics and their awareness of effective digital pedagogy. The study strongly recommends integrating DPW into physical science teaching, particularly when traditional laboratory work is impractical. Unlike conventional teaching that merely transmits information, physical science education requires hands-on, practical observation to support theoretical concepts and promote meaningful learning. DPW bridges this gap, ensuring that students receive a robust and engaging science education, regardless of the constraints of the physical laboratory environment.